(untitled) (PIONIR: JURNAL PENDIDIKAN, 2021)
Islamic basic education is a formal initial education program for all Indonesian citizens, every Indonesian citizen is required to have education for nine years. It can be said that the first nine years of schooling of children are referred to as the initial level of basic education. Basic education is not only Elementary School / Madrasah Ibtida’iyah but junior high school / Madrasah Tsanawiyah is also included in the category of basic education, basic education has two types, namely public and private Islamic primary education. During this time educational development has experienced a very acute disorientation in quality and excellence to prepare graduates who are able to manage the knowledge they have acquired. There are many problems that occur in basic Islamic education in Indonesia, ranging from teaching staff, human resources, capacity, facilities and infrastructure, low quality education quality and discriminatory funding problems seen from the provision of unequal funding. Thematic is a government business or program that can reflect the problems of basic Islamic education with the main subject of MI, with thematic learning problems in basic education can be minimized through learning activities that are linked to the daily activities of students. The method used in this research is literature study, in the form of research whose objects are literature works, namely scientific journals, books, articles in the mass media, and statistical data.